ANALISIS KESULITAN BELAJAR BAHASA ARAB DENGAN METODE ISTIMA’ (STUDI ANALISIS DESKRIPTIF PADA SISWA KELAS VIII UNGGUL MADRASAH TSANAWIYAH NEGERI 2 BANDAR LAMPUNG TAHUN PELAJARAN 2011/2012): ANALISIS KESULITAN BELAJAR BAHASA ARAB DENGAN METODE ISTIMA’ - Doni Sastrawan (An Naba, 2019)
Language functions as a mean for someone to give opinion, ideas, and thought to other people. With a language, human can create a community and culture. Arabic language is one of languages that are slowly learned by many scholars in the world. In Indonesia, this language is also learnt because this country’s major religion is Islam in which it has Qur’an as the holy book and the Quran is written in Arabic language. The method of study used is the descriptive analysis method. This is a method in taking sample from a population and by using questionnaire as a tool to collect the data. In this study, the data and information are collected from the respondents by using questionnaire. The targeted population in this study is 74 people including the VIII class students of MTs Negeri 2 Bandar Lampung (excellent class 1 for 35 students and excellent class 2 for 38 students). The sample taken by the researcher in this study is 25 students as needed. This study used qualitative approach while the method is descriptive analysis. The data collection technique used in this study is by giving questionnaire. The sampling technique used by the researcher is accidental sampling, which is the technique in defining sample based on the spontaneities factor.